Factors Related to Depressive Symptoms in Mothers of Technology-Dependent Children - Toly, Valerie Boebel (Issues Ment Health Nurs, 2015)
Mothers caring for technology-dependent children at home often suffer clinically significant and unrecognized depressive symptoms. The study aim was to determine factors related to elevated depressive symptoms and provide information to target interventions that assists mothers in self-management of their mental health. Secondary data analysis from a descriptive, correlational study of 75 mothers was performed. Hierarchical multiple regression analysis results indicate that younger, unpartnered mothers with lower normalization efforts and personal resourcefulness, and less care hours had increased depressive symptoms. The importance of personal resourcefulness and the potential for a resourcefulness training intervention to reduce depressive symptoms are discussed.